THE APPLICATION OF NON-TAXABLE SALES VALUE OF TAX OBJECT IN THE CALCULATION OF LAND AND BUILDING TAX - Nobertus Purnomo Lastu; Widya Indah Nurmalasari (Politeknik Ubaya, 2023)
Land and Building Tax is given on land and building ownership for state revenue. While the Selling Value of Non-Taxable Tax Objects (NJOPTKP), is one of the components in calculating Land and Building Tax (L&B). Calculating Land and Building Tax determined by Sales Value of Tax Object (NJOP) and NJOP increases every year. The problem is whether or not NJOPTKP, used as a deduction for NJOP, influences the calculation of L&B Tax due to the absence of material changes from the deduction. In this study, NJOPTKP of L&B Tax was analyzed using a qualitative descriptive dan quantitative method by comparing changes in Non-Taxable Income of Income Tax (PTKP), and L&B taxes between Indonesia and other countries. The analysis results indicated that economic quantities such as inflation, Regional Minimum Wages and changes in PTKP of Income Tax were not related to changes in NJOPTKP. The application of L&B Tax does not consider the status of land and buildings (whether or not it is productive) and the family status of the subjects who own the land and buildings. As a result, NJOPTKP does not have a material meaning for the calculation of L&B Tax due to the absence of a significant adjustment when compared to the increase in the NJOP on Rural and Urban Sectoral L&B Taxes (PBB-P2) and Plantation, Forestry and Mining Sectoral L&B Taxes (PBB-P3).